ANALISIS PENGARUH PARKIR LIAR TERHADAP PENDAPATAN PEMILIK USAHA DI KOTA BANDA ACEH - Rihan Varizie; Talbani Farlian (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThis research aims to examine how the influence wild parking income persons business owners who have businesses in the center of the economy. The methods used in this research uses qualitative, descriptive methods of analysis. This method is used to analyze the size of the Central leanings, dispersion and distribution of data, such as average, median and variance, as well as maximum and minimum values. The data obtained will also explain how the influence wild parking income persons business owners in the city of Banda Aceh. The results showed that the wild parking that is in the place of business of the respondents did not give negative impact on incomes of business owners. Wild parking lot also does not affect the consumer's visit to places of business respondents, because the fares charged by the custodian of the wild parking not too big of an official tariff, thus making consumers do notburdenedto return to the place of business.Keywords: ilegal parking, income.